EVALUASI KEMAMPUAN MEMBACA DAN MENULIS RAPI PADA SISWA JENJANG KELAS II SDN 095259 MANDARO - Mala Hayati Siahaan; Anjar Wati; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2022)
This research is a class action research (Classroom Action Research). The research was conducted in class II of SDN 095259 Mandaro in semester I of the 2022/2023 academic year starting on September 19 2022 to September 28 2022. The research data is in the form of primary data sources, namely: students, teachers, parents or related parties and secondary data sources, namely: observation sheets, documents, and notes. Data collection techniques were carried out by observing during the learning process to find out student activities, research documents by collecting written data, lists of formative values, and notes. This data collection is to find out about the student's personality. The data analysis technique used is an interactive qualitative data analysis technique. The results of this study were carried out by evaluation to measure students' ability to read and write neatly which was applied at SD095259 Mandaro N. In implementing this evaluation, it can measure students' ability to read and write neatly at the school level in class II SD. Recommendations that can be conveyed are that in choosing the method to be applied in the learning process in the classroom, the teacher should first know the limits of the abilities and conditions of the students. Both the conditions that exist in the classroom and outside the classroom by carrying out this evaluation method.